Design of tunnel pressure monitoring system of coal mine based on ZigBee - LI Xuezhe; HU Xingzhi; FENG Xiaohui; ZHANG Youdong (Gong-kuang zidonghua, 2014)
In view of problems of low measuring precision, bad reliability, bad scalability of nodes and non-automatica uploading, analyzing and processing for measuring results, a tunnel pressure monitoring system of coal mine based on ZigBee was designed. The system uses sensor nodes to realize accurate measurement for tunnel pressure, and measuring result is sent to convergent node which sends the measuring result to surface monitoring computer, so as to realize real-time and reliable monitoring for the tunnel pressure. The test result shows that the system can realize precision measurement for stress of anchor and can upload the measuring result real-timely.